2014
DOI: 10.1021/cs500393x
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Bimetallic Asymmetric Catalysis: Comparison of a Planar Chiral Ruthenocene Bis-Palladacycle to the Corresponding Ferrocene

Abstract: Cooperative asymmetric catalysts often offer advantages in terms of activity, stereoselectivity, and generality as compared to more traditional single point activation catalysts. In cooperative bimetallic catalysis, the intermetallic distance is a crucial parameter for the outcome of a reaction and an optimal synergy of both metal centers. We have recently developed a number of catalytic asymmetric reactions, which are efficiently catalyzed by a planar chiral ferrocene based bispalladacycle and for which the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 85 publications
0
18
0
Order By: Relevance
“…The Michael addition products were summarized and listed in Scheme 30. Three types of enolates were used: α ‐cyanoacetates [ 66‐67 ] ( 32a , 32b ), azlactones [ 68‐73 ] ( 33a — 33c ) and isoxazolinones [ 74 ] ( 33d ). In the case of α ‐cyanoacetates, FBIP or FIP could deliver different diastereoisomers as the major product, showing the stereodivergency of the two palladacycle catalysts.…”
Section: Bidentate Imidazoline Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Michael addition products were summarized and listed in Scheme 30. Three types of enolates were used: α ‐cyanoacetates [ 66‐67 ] ( 32a , 32b ), azlactones [ 68‐73 ] ( 33a — 33c ) and isoxazolinones [ 74 ] ( 33d ). In the case of α ‐cyanoacetates, FBIP or FIP could deliver different diastereoisomers as the major product, showing the stereodivergency of the two palladacycle catalysts.…”
Section: Bidentate Imidazoline Ligandsmentioning
confidence: 99%
“…Based on Overman rearrangement that has been studied in detail, the catalytic reactivity of the analogous ruthenocene palladacycles 35 was reported in 2014. [ 73 ] Ruthenocene has a longer distance betwen two Cp rings than ferrocene (3.58 Å vs. 3.29 Å), thus the distance of two palladium centers also increases (Figure 8). This is of great importance in bimetallic catalysis, especially for those substrates binding with both metal centers, as appropriate distance could eliminate potential strain and promote effective binding.…”
Section: Bidentate Imidazoline Ligandsmentioning
confidence: 99%
“…194,195 This constitutes a significant practical advance, because unlike benzamides, the trihaloacetamide products are readily deprotected to afford the primary allylic amines in high yield. Peters and coworkers later reported that metallocenyl oxazoline and imidazoline catalysts permit a 100-fold reduction in catalyst loadings for both the Eand the less reactive Z-isomer courtesy of [PPFOP-Cl] 2 (318), 196 [RuBIP-Cl] 2 (319a) 197 and FIP-Cl (320) 198 (entries 8, 9 and 11). 199,200 Interestingly, the activated forms of [PPFOP-Cl] 2 (318) and FIP-Cl (320) feature a palladium(III) center and represent the first palladium(III) complexes to be employed in enantioselective catalysis.…”
Section: Syn Thesismentioning
confidence: 99%
“…More than one billion people, which amounts to onesixth of the world's population, are affected by NTDs within 149 countries. 1,2 Even though the morbidity exceeds the mortality, more than half a million deaths per year are caused by NTDs. 3 Among NTDs, worm infection, or helminthiasis, has been the target of global elimination programs.…”
Section: Introductionmentioning
confidence: 99%